2015
DOI: 10.11606/issn.2176-7262.v48i6p549-556
|View full text |Cite
|
Sign up to set email alerts
|

Association of falls, fear of falling, handgrip strength and gait speed with frailty levels in the community elderly

Abstract: Introduction: The Frailty Syndrome is not synonymous with disability, but may be a precursor of etiological and physiological dysfunction, which affects mobility before causing reduced functional capacity, explaining conditions of weakness, weight loss, and abnormal gait. Study design: This is an analytical, observational, cross-sectional study. Objective: To verify the association of handgrip strength, gait speed, fear of falling, and falls with the level of frailty. Methods: Study consisting of 54 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
2
8
0
2
Order By: Relevance
“…Studies (31,33,35,55,59,(65)(66) showed that frailty is associated with reduced GS, and these findings are in agreement with another study. Data from the English Longitudinal Study of Aging (ELSA) showed that 90% of elderly classified as fragile had reduced GS (84) .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Studies (31,33,35,55,59,(65)(66) showed that frailty is associated with reduced GS, and these findings are in agreement with another study. Data from the English Longitudinal Study of Aging (ELSA) showed that 90% of elderly classified as fragile had reduced GS (84) .…”
Section: Discussionsupporting
confidence: 84%
“…As observed in the different studies, even though there is no established consensus for GS measurement, there was a predominance of distance of 4.6 meters (23,34,38,(39)(40)42,(44)(45)50,(58)(59)(60)(73)(74) , and cutoff points for reduced GS were defined by the lowest quintile value (7,34,40,42,44,49,54,57,59,65,69,72,75) . These studies follow the procedure/protocol of the study (6) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations